(untitled) (Multidisciplinary Journal of Science and Technology, 2023)
Changes in heart rate variability, identified using the cardiorhythmography method, indicate the severity of autonomic disorders, characterized by a sympathetic-parasympathetic imbalance with a predominance of sympathetic and suprasegmental autonomic influences, as well as a violation of adaptive mechanisms in patients with HT; these changes are more pronounced in females . In both groups there was a large percentage of patients with such symptoms - 89.1% and 80.7%, respectively, in MG and SG.